E-CHARACTER ASSESSMENT BASED ON PROFIL PELAJAR PANCASILA FOR ELEMENTARY SCHOOL - Nurhasanah, Nina; Sarifah, Iva; Hasanah, Uswatun (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2024)
Implementing the character of education for elementary schools in Indonesia requires e-assessment using the dimensions of the Pancasila student profile to make it easier for teachers to use it. In contrast, e-assessment still needs to be created. This research aims to research and develop an electronic instrument for assessing student character in elementary schools based on the Pancasila Student Profile. The research method used is the 4-D model research and development method (Four-D Model) introduced by S. Thiagarajan. The research was conducted in elementary schools in five areas of DKI Jakarta, including Central Jakarta, East Jakarta, South Jakarta, North Jakarta, and West Jakarta, with 762 students as respondents. The instrument used was a questionnaire. This character e-assessment instrument based on the Pancasila Profile was validated with results obtained from validation scores from material experts of 76% and language experts of 91%, so this character e-assessment instrument is said to be scientifically feasible. The research produced a prototype model of the character e-assessment instrument that has been validated. This research indicates that using a character assessment based on the Pancasila Profile is feasible and easy for students and teachers.